Giant immature sacrococcygeal teratoma with early recurrence and lung metastases: A case report - Kyoko Matsuki; Kenji Santo; Takashi Sasaki; Hiroyuki Fujisaki; Akihiro Yoneda (Elsevier, 2024)
Introduction: Neonatal sacrococcygeal teratoma (SCT) results in poor outcomes if it is associated with preterm delivery and an immature histology. Furthermore, some patients experience recurrence, generally one to two years later. We herein present a preterm infant case of an immature SCT with metastatic recurrence within two months of the initial resection. Case presentation: A neonate with prenatally diagnosed SCT was born at 28 weeks' gestation with a birth weight of 2337 g. The tumor measured 18 × 9 × 8 cm in diameter, and it was predominantly solid and hypervascular. Postnatally, the patient presented with anemia and coagulopathy requiring a massive transfusion presumably due to intratumoral hemorrhage. Surgical resection was performed at 12 days of age. The tumor was histologically diagnosed to be an immature teratoma. The alpha-fetoprotein (AFP) levels decreased but increased thereafter on postoperative day 68. Computed tomography revealed both local recurrence and bilateral lung metastases. During chemotherapy, all secondary lesions were enlarged. We resected the lesion in the right lung, which was histologically diagnosed as mature teratoma. Even after switching chemotherapy protocols, the residual lesions were progressive. We resected the lesion from the left lung. Following another course of chemotherapy, we resected the presacral recurrent tumor, which was histologically confirmed as a mature teratoma. The patient has not shown any signs of a re-recurrence for 6 years. Conclusion: This case highlights the fact that immature sacrococcygeal teratomas can recur and metastasize as early as two months after the initial resection.